Growth Kinetics of Ethidium Bromide Mutagenized Lipomyces starkeyi Strains - Micky, Vincent; Latifah, Suali; AfIzul Safwan, Azahari; Patricia Rowena, Anak Mark Baran Saging; Elexson, Nillian; Lesley Maurice, Bilung (Akademia baru, 2018)
Micky Vincent1,*, Latifah Suali1, Afizul Safwan Azahari1, Patricia Rowena Mark Baran1, Elexson Nillian1, Lesley Maurice Bilung1